Multiplier–Accelerator Interaction in the Presence of an Underground Economy and Taxation. (May 2018) - Soldatos, Gerasimos T.
This article introduces the underground economy into a standard multiplier-accelerator model with linear progressive income taxation. The main results are that this introduction increases the instability of the overall economy towards chaos, that tax policy plays a critical role in preserving stability even if in the sense of a uniform cycle and that the operation of the accelerator may be countering the negative effect of tax evasion on tax revenue. JEL Classification: O17, E32, H24